Motivational Interviewing is “” What Matters: Integrating Motivational Interviewing Spirit and Skills into What Matters to You? Conversations - Damara Gutnick MD; Sarah McNeilly BA (Journal of Patient Experience)
As the What Matters To You (WMTY) movement spreads across the globe, countless clinicians have been inspired to ask their patients its eponymous question: what matters to you ? Still, some clinicians remain apprehensive about asking what matters , worried that it can open a Pandora's box of problems too big for any one person to solve. This paper argues that embracing the spirit and skills of motivational interviewing (MI) can help and provides practical recommendations for navigating the synergistic uses of MI and WMTY.